Programming with Microsoft Visual Basic 2015 - Zak, Diane (Cengage Learning, 2016)
This edition places particular emphasis on GUI design skills and responsive design. To ensure your success, the book is available with an optional MindTap, which includes an eBook, interactive quizzing, study tools, and dynamic videos created and narrated by the author